Radiation resistance of praseodymium-doped aluminum lithium fluorophosphate scintillator glasses for laser fusion experiments. (1st January 2023) - Shinohara, Keito; Empizo, Melvin John F.; Cadatal-Raduban, Marilou; Yamanoi, Kohei; Shimizu, Toshihiko; Yoshimura, Masashi; Sarukura, Nobuhiko; Murata, Takahiro; Uy, Mayrene A.; Abe, Hitoshi; Yoshikawa, Akira; Boulon, Georges; et al.
Abstract: We report the gamma ( γ )-ray radiation resistance of praseodymium (Pr 3+ )-doped aluminum lithium fluorophosphate scintillator glasses. For its assessment as a scintillator material for laser fusion experiments, a 20Al(PO3 )3 -80LiF-PrF3 (Pr 3+ -doped APLF) glass was irradiated with γ -rays from a cobalt-60 ( 60 Co) source resulting in an absorbed dose of 5.2 kGy. Although γ -ray-irradiation results in increased absorption due to phosphorus-oxygen hole centers (POHCs) and PO3 2− electron centers (PO3 ECs), these radiation-induced defects do not modify the glass emission as both non-irradiated and γ -ray-irradiated glasses exhibit similar emission spectra and decay times under optical and X-ray excitation. The emission peaks observed also correspond to the different interconfigurational 4f5d → 4f 2 and intraconfigurational 4f 2 transitions of Pr 3+ ions which are neither oxidized nor reduced by irradiation. Our results show that Pr 3+ -doped APLF glass still maintains its characteristic fast decay time and that γ -ray irradiation does not affect the glass scintillation mechanisms.